Simultaneous Infection of the Skin Surface and Dermal Tissue with Two Different Fungus Mimicking Pyoderma Gangrenosum: A Case Report - Jia QY; Song YG; Li XQ; Mu ZL; Li RY; Li HM (Dove Medical Press, 2021)
Qiu-Yu Jia,1 Ying-Gai Song,2 Xiang-Qian Li,1 Zhang-Lei Mu,1 Ruo-Yu Li,2 Hou-Min Li1 1Department of Dermatology, Peking University People’s Hospital, Beijing, People’s Republic of China; 2Department of Dermatology, Peking University the First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Hou-Min LiDepartment of Dermatology, Peking University People’s Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People’s Republic of ChinaTel +86 (424) 390-2625Email lhoumin@sina.cnAbstract: Mucormycosis is an opportunistic fungal infection driven by subphylum Mucormycotina. Cutaneous mucormycosis is the third most common presentation of mucormycosis, and its characterized presentation is an indurated plaque that rapidly evolves to necrosis. Trichophyton rubrum is one of the most common dermatophytes that mainly cause superficial infections and seldom induce deep infections. The present report presents a case of cutaneous fungal infection, in which two kinds of fungus were isolated, and the skin lesion mimicked pyoderma gangrenosum. Trichophyton rubrum was isolated from the crust and hyphae of subphylum Mucormycotina were found in dermal tissue. The irregular systemic and topical use of steroid therapy is the possible cause of the mixed fungal infection in this patient, suggesting the importance of regular steroid therapy.Keywords: cutaneous mucormycosis, Trichophyton rubrum infection, cutaneous infection, lower leg, steroid therapy